Scrutinizing Perseroan Perorangan: The Brainchild of Societas Unius Personae in the Realm of Indonesian Company Laws (Lex Scientia Law Review, 2022)
The Indonesian government has long been committed to developing the business conditions, particularly for micro, small, and medium-sized enterprises (MSMEs). The debut of a single-person limited company (perseroan perorangan) is one of the numerous ambitions of this crucial aspiration. Debates circling this novel kind of company in Indonesia remain a heated debate between practitioners, jurists, scholars, and the government. This article endeavors to elucidate these debates by concentrating on the legal theories encompassing company laws, the practice of single-member limited liability companies overseas and domestically and scrutinizing the single-person limited companies amid the contemporary Indonesian legal dan regulatory regime. This research utilizes doctrinal legal study and secondary data. Dogmatic literature reviews are carried out on scholarly works concerning the subject matter, and the analysis is carried out using the qualitative method. This inquiry reveals that the current single-person limited companies in Indonesia are supported adequately by several legal theories. This sort of company has been exercised in numerous nations, mainly in Europe. There is also room for legislative and executive development and juridical enhancement to ultimately maximize the company's potential.